2021
DOI: 10.3390/cancers13112548
|View full text |Cite
|
Sign up to set email alerts
|

High Serum PD-L1 Levels Are Associated with Poor Survival in Urothelial Cancer Patients Treated with Chemotherapy and Immune Checkpoint Inhibitor Therapy

Abstract: Serum PD-L1 (sPD-L1) levels are associated with prognosis in various tumors but has not yet been investigated in advanced bladder cancer. We assessed pretreatment serum samples from 83 BC patients who received platinum chemotherapy and from 12 patients who underwent immune checkpoint inhibitor (ICI) therapy. In addition, on-treatment samples from further therapy cycles were collected during chemotherapy (n = 58) and ICI therapy (n = 11). Serum PD-L1 levels were determined using ELISA. High baseline sPD-L1 leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 33 publications
5
30
0
Order By: Relevance
“…Supporting data for increased levels of sPD-L1 in patients with metastatic disease has also been reported in other cancer types, such as non-small cell lung cancer and renal cell cancer [ 28 , 29 ]. High sPD-L1 levels were also associated with all-cause mortality in the present study, which is in line with data from Krafft et al, reporting sPD-L1 as an independent predictor of overall survival in patients with BC [ 21 ]. However, no association between sPD-L1 and cancer-specific death was found in the present study, possibly due to the small number of events, leaving the study without power for investigating this association.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Supporting data for increased levels of sPD-L1 in patients with metastatic disease has also been reported in other cancer types, such as non-small cell lung cancer and renal cell cancer [ 28 , 29 ]. High sPD-L1 levels were also associated with all-cause mortality in the present study, which is in line with data from Krafft et al, reporting sPD-L1 as an independent predictor of overall survival in patients with BC [ 21 ]. However, no association between sPD-L1 and cancer-specific death was found in the present study, possibly due to the small number of events, leaving the study without power for investigating this association.…”
Section: Discussionsupporting
confidence: 93%
“…These results suggest that serum sPD-L1 levels increase with a more aggressive disease. Krafft et al, reported significantly higher levels of serum sPD-L1 among patients with high stage BC (T3–T4) compared to patients with low stage disease (T0–T2), although they found no association between sPD-L1 and lymphatic or visceral metastases [ 21 ]. Supporting data for increased levels of sPD-L1 in patients with metastatic disease has also been reported in other cancer types, such as non-small cell lung cancer and renal cell cancer [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was an increasing body of evidence suggested that immune regulation played an important role in bladder cancer, including PD-1, PD-L1, tumor-associated macrophages, myeloid-derived suppressor cells, regulatory T cells and so on [ 6 ]. Ulrich et al demonstrated that higher pretreatment serum PD-L1 (sPD-L1) levels were related to the poor prognosis in patients following platinum and immune checkpoint inhibitor treatments [ 54 ]. Jiang et al revealed that M2 and PD-1-positive Tumor-associated macrophages were connected with poor clinical results in muscle invasive bladder cancer patients, and the blinding of PD-1 and CD68 could stimulate tumor growth [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Soluble PD-1/PD-L1 was suggested as a diagnostic, therapeutic and prognostic biomarker in different cancers (summarized in [ 10 ]), indicating, e.g., an impaired outcome and treatment response in patients with multiple myeloma [ 11 ]. Moreover, in a series of papers, different authors recently suggested a role of sPD-L1 as a biomarker in very different cancer entities and have suggested a diagnostic, prognostic and predictive role of this molecular marker in cancers originating from the urothelium, lung and brain [ 12 , 13 , 14 ]. In addition, sPD-L1 was found to be a prognostic marker in gastrointestinal stromal cancers and gastric cancers [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%